Pentacoordinated diorganotin(IV) complexes resulting from tridentate (NOO) donor Schiff bases: Synthesis, characterization, in vitro antioxidant, antimicrobial activities, and QSAR studies. (10th September 2020) - Devi, Jai; Pachwania, Sushila; Yadav, Jyoti; Kumar, Ashwani
Abstract: A series of diorganotin(IV) complexes of type R2 SnL, (where R = Me, Et, Bu and Ph) were prepared by the reaction of tridentate (NOO) donor Schiff base ligands with diorganotin(IV) dichloride in an equimolar ratio. The products were characterized by various spectroscopic techniques and physical and analytical methods (UV–vis, FTIR, NMR, fluorescence, elemental analysis). Spectroscopic data suggest that the Schiff base acts as a tridentate ligand (NOO) coordinated with a central tin atom via two oxygen and one imine nitrogen atom in a pentacoordinated fashion. The synthesized compounds were assayed for their in vitro antimicrobial activity against bacterial and fungal strains. All the compounds displayed promising results with the complexes being more potent than free ligands. The antioxidant activity of the compounds was determined by interaction with 2, 2-diphenyl-1-picrylhydrazyl free radical. Complex Ph2 SnL 3 (16 ) was found to have the most potential antimicrobial activity against all tested strains and also exhibited excellent antioxidant activity. Quantitative structure–activity relationship of compounds was studied for antimicrobial activity with molar refractivity indices as significant statistical parameter. Graphical Abstract: